The Effect of Work Culture and Employee Work Quality on Organizational Commitment with Motivation as a Moderating Variable at Bank Indonesia Representative Office of North Sumatera Province - Antoni; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze how Work Culture and Work Quality influence Organizational Commitment, with Motivation acting as a moderating factor at the Bank Indonesia Representative Office in Medan, North Sumatra. Quantitative methods were used in this study, specifically by using Structural Equation Modeling (SEM) analysis through SmartPLS 3.0 software. Participants included employees from the Bank Indonesia Representative Office in Medan, who were selected through a purposive sampling method. The findings indicate that Work Culture and Job Quality significantly influence Organizational Commitment, although their effects are relatively weak, which limits their ability to increase commitment. The analysis shows that motivation negatively moderates the relationship between Work Culture and Organizational Commitment, suggesting that motivation reduces the bond between these two elements. Furthermore, motivation appears to have only a small strengthening effect on the relationship between Work Quality and Organizational Commitment. Furthermore, the direct impact of Motivation on Organizational Commitment is also significant, although with a minimal contribution. These results suggest the possibility that other elements beyond the research variables may have a greater influence on employee commitment.